Drain water heat recovery storage-type unit for residential housing. (25th June 2016) - Torras, S.; Oliet, C.; Rigola, J.; Oliva, A.
Highlights: A DWHR unit performance has been analysed at different flow rates and temperatures. The DWHR is capable to recover from 34% to 60% of the energy available. The transient heat recovery process of a DWHR prototype is characterised in detail. The in-tank water has been analysed numerically using 3D transient CFD. The heat loss test revealed its limitations for long-term storage applicability. Abstract: The drain water heat recovery (DWHR) system is an interesting household technology to reduce energy costs and environmental impact. The objective of the utilisation of these devices is the recovery of the waste heat from domestic warm drain water, and transferring it to cold water entering the house. A drain water heat recovery unit has been built in this work. The authors are using both numerical and experimental tools to design and study the performance of this device, focusing on the analysis of a specific drain water heat recovery storage-type based on a cylindrical tank with an internal coiled pipe. The numerical simulation has been performed using an in-house platform, where the different elements of the DWHR storage are linked to solve the system. On the other hand, an experimental infrastructure has been developed to analyse of the system, which has been instrumented to provide detailed information of its heat recovery and storage capacities and temperature map. Different internal flow rates and operational temperatures have been studied. From the results obtained it can be said that the device shows interesting heat recovery and storage capacities, while the numerical platform shows promising comparison results against the experiments.